Overexpression of cyclo-oxygenase-2 is an independent predictor of unfavourable outcome in node-negative breast cancer, but is not associated with protein kinase B (Akt) and mitogen-activated protein kinase (ERK1/2, p38) activation or with Her-2/neu signalling pathways. Issue 7 (23rd February 2006) - Schmitz, K J; Callies, R; Wohlschlaeger, J; Kimmig, R; Otterbach, F; Bohr, J; Lee, H-S; Takeda, A; Schmid, K W; Baba, H A
Abstract : Background and aim: The production of prostaglandins is regulated by cyclo-oxygenases (COXs), which also have a role in tumour development and progression in various malignancies, including breast cancer. The mechanisms by which COX-2 contributes to unfavourable prognosis are still poorly understood. The association between expression of COX-2 and possible linked signalling pathways—namely, Akt, extracellular regulated kinases (ERK1/2), the stress-activated kinase p38 or Her-2/neu—is assessed in a series of 113 node-negative breast cancers. Results: COX-2 was identified as an independent prognostic factor (p = 0.034) in node-negative breast cancer by survival analysis. The lack of a relationship between COX-2 expression and activated Akt, Erk1/2, p38 and Her-2/neu was indicated by statistical analysis. Conclusions: The prognostic effect of COX-2 expression on lymph node-negative breast cancer is confirmed—COX-2 is probably not regulated by HER-2, Akt, Erk1/2 or p38. Further studies are necessary for the elucidation of the signalling pathways responsible for the modification of COX-2 expression and the increased aggressiveness of breast cancers overexpressing COX-2.